Konseling Klasikal Berbantuan Musikalisasi dalam Mengatasi Perilaku Bullying - Anjelli Nur Aisyah; Kusnadi Kusnadi (Journal of Society Counseling, 2025)
Bullying behavior has become a serious issue among children, especially in the educational environment. Bullying is an aggressive behavior that is repeatedly carried out with the intention of harming or intimidating others, leading to negative impacts on both the victim and the perpetrator. The consequences can be severe, ranging from discomfort and insecurity to deep trauma. Therefore, appropriate solutions are needed to reduce bullying behavior among children. Classical counseling assisted by musicalization is a creative solution to address this issue. This study, titled "The Role of Classical Counseling Assisted by Musicalization in Overcoming Bullying Behavior Among Children at TPA Neighborhood Kemas RT 8, Palembang City," aims to investigate the role of classical counseling assisted by musicalization in addressing bullying behavior among children in TPA Neighborhood Kemas RT 8, Palembang City. This research employs a descriptive method with a qualitative approach. Data were collected through interviews, observations, and documentation. The results show that classical counseling assisted by musicalization can help reduce bullying behavior, enhance children's ability to manage emotions, and develop positive behavior. Additionally, this study indicates that this counseling method increases children's awareness of the importance of respecting and appreciating differences. Therefore, this study recommends that classical counseling assisted by musicalization be integrated into educational programs at TPA Neighborhood Kemas RT 8, Palembang City. Furthermore, it suggests that educators and parents collaborate in developing effective counseling programs to address bullying behavior among children.